2020
DOI: 10.1002/anie.202003104
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Guerbet Reaction to Access Chiral Alcohols

Abstract: The first example of an asymmetric Guerbet reaction has been developed. Using commercially available, classic Noyori RuII‐diamine‐diphosphine catalysts, well‐known in asymmetric hydrogenation, racemic secondary alcohols are shown to couple with primary alcohols in the presence of a base, affording new chiral alcohols with enantiomeric ratios of up to 99:1. Requiring no reducing agents, the protocol provides an easy, alternative route for the synthesis of chiral alcohols. Mechanistic studies reveal that the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 152 publications
(5 reference statements)
6
39
0
2
Order By: Relevance
“…Based on our previous studies [10q, 12] and the literature, [11] the mechanism of this asymmetric hydroamination may be similar to that of the previously reported formal anti‐Markovnikov hydroamination of allylic alcohols [11–12] . As illustrated in Figure 1 d, the chiral Ru catalyst is likely to dehydrogenate the allylic alcohol to afford a Ru hydride complex and an α,β‐unsaturated ketone intermediate, which undergoes aza‐Michael addition to give a β‐amino ketone intermediate.…”
Section: Figuresupporting
confidence: 80%
See 3 more Smart Citations
“…Based on our previous studies [10q, 12] and the literature, [11] the mechanism of this asymmetric hydroamination may be similar to that of the previously reported formal anti‐Markovnikov hydroamination of allylic alcohols [11–12] . As illustrated in Figure 1 d, the chiral Ru catalyst is likely to dehydrogenate the allylic alcohol to afford a Ru hydride complex and an α,β‐unsaturated ketone intermediate, which undergoes aza‐Michael addition to give a β‐amino ketone intermediate.…”
Section: Figuresupporting
confidence: 80%
“…We recently showed the feasibility of formal anti‐Markovnikov hydroamination of allylic alcohols with an achiral iron catalyst via hydrogen borrowing [12] . Our further work using a similar approach has revealed that the Guerbet reaction can be made enantioselective with a chiral Ru‐diamine‐diphosphine catalyst, in which an intermediary ketone is reduced to a chiral alcohol product [10q] . We envisioned that such chiral Ru‐diamine‐diphosphine catalysts could be utilized for the formal hydroamination of racemic secondary allylic alcohols, which would produce chiral γ‐amino alcohols (Figure 1 d).…”
Section: Figurementioning
confidence: 96%
See 2 more Smart Citations
“…[b] The enantiomeric ratio (er) was determined by HPLC analysis of pure isolated product, and the absolute configuration was determined by X-ray crystallography. [26] [c] R-4a was the major product.…”
Section: Substrate Scope Gram-scale Reaction and Synthetic Applicationmentioning
confidence: 99%